The Effects of Skipping Rope Exercise, Brisk Walking Exercise, and Weight Training on Cardiorespiratory Endurance in Physiotherapy Students - Kusumaningtyas, Mei; Handari, Herdianty Kusuma (Indonesian Journal of Medicine, 2021)
Background: There is a mutually influencing relationship between physical activity and fitness level, especially the cardiorespiratory endurance component. Types of exercise that can increase cardiovascular endurance are skipping rope, fast walking, and weight lifting. Thoses exercises are simple and easy to do. This study aimed to determine whether or not there was a difference in influence and which one was the most influential between skipping rope, fast walking, and weight training on the cardiorespiratory endurance of physiotherapy students.Subjects and Method: This was a randomized control trial study, conducted at the Department of Physiotherapy, School of Health Polytechnics, Ministry of Health, Surakarta, from July to August 2020. A total of 36 students was selected by random sampling, and allocated into 4 groups consisted of 9 students: (1) Skipping rope exercise group; (2) Fast walking group; (3) Weight training group; and (4) Control group. The dependent variable was cardiorespiratory endurance. The independent variable was skipping rope, fast walking, and weight training. Cardiorespiratory endurance was measured by the Cooper method to measure VO2 max. Data were analyzed using paired t test, Wilcoxon, and One Way ANOVA.Results: After intervention, cardiorespiratory endurance was increased in all intervention groups. There was no statistically significant different effects on cardiorespiratory endurance between skipping rope group (Mean= 1.48; SD= 0.42), fast walking group (Mean= 1.42; SD= 0.30), weight training group (Mean= 1.38; SD= 0.22), and control group (Mean= 1.17; SD= 0.28) with p value of 0.218.Conclusion: Skipping rope and weight training significantly increase cardiorespiratory endurance. There is no difference in the effect of skipping rope, fast walking, and weight training on cardiorespiratory endurance.Keywords: skipping rope, fast walking, weight training, cardiorespiratory endurance, cooper test, VO2maxCorrespondence: Mei Kusumaningtyas. Physiotherapy Department, Health Polytechnics, Ministry of Health. Jl. Adi Sumarmo, Tohudan, Colomadu, Karanganyar, 57173, Central Java. Email: meikusumaningtyas@gmail.com. Mobile: 085725646444.Indonesian Journal of Medicine (2021), 06(04): 423-429https://doi.org/10.26911/theijmed.2021.06.04.08